Restoration of cytosolic calcium inhibits Mycobacterium tuberculosis intracellular growth: Theoretical evidence and experimental observation. (7th July 2019) - Gupta, Ankur; Das, Phonindra Nath; Bouzeyen, Rania; Karmakar, Sonali Porey; Singh, Ramandeep; Bairagi, Nandadulal; Chatterjee, Samrat
Highlights: Model studied to capture mechanisms by which Mtb suppress phagosome-lysosome fusion. Some plausible methods are identified to restore PI3P oscillations which is necessary for phagosome maturation and killing of Mtb. RyR2 agonist caffeine inhibits growth of intracellular Mtb in macrophages validation to our model result. Abstract: Mycobacterium tuberculosis (Mtb) is a highly successful intracellular pathogen because of its ability to modulate host's anti-microbial pathways. Phagocytosis acts as the first line of defence against microbial infection. However, Mtb inhibits Phosphatidylinositol 3-phosphate (PI3P) oscillations which is required for phagolysosomal fusion. Here we attempted to understand the mechanisms by which Mtb eliminates phagosome-lysosome fusion. To address this, we built a four dimensional ordinary differential equation model and explored the contribution of PI3P during Mtb phagocytosis. Using this model, we identified some sensitive parameters that influence the dynamics of host-pathogen interactions. We observed that PI3P dynamics can be controlled by regulating the intracellular calcium oscillations. Some plausible methods to restore PI3P oscillations are ER flux rate, recruitment rate of proteins, like Rab GTPase, and cooperativity coefficient of calcium dependent consumption of calmodulin. Further, we investigated whether modulation of these pathways is a potential therapeutic intervention strategy. Here we showed that RyR2 agonist caffeine stimulated calcium influx and inhibited growth of intracellular Mtb in macrophages. Taken together, we demonstrate that modulation of host calcium level is a plausible strategy for killing of intracellular Mtb.